2011
DOI: 10.1007/s00423-011-0854-z
|View full text |Cite
|
Sign up to set email alerts
|

Multivisceral and standard resections in colorectal cancer

Abstract: Multivisceral resections are associated with the same 5-year survival as standard resections. Therefore, the aim to perform a R0 resection should always be the main goal in surgery for colorectal cancer. In planned operations, a laparoscopic approach is justified in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 20 publications
9
40
2
1
Order By: Relevance
“…In this study, invasion of other organs was confirmed by pathological examination in 53.5% of the samples, which was similar to the majority of the other series (range 34 to 58%) 11. Peritumoral inflammation may result in adhesions that are indistinguishable from true malignant invasion of proximal organs and structures during the surgical procedure.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, invasion of other organs was confirmed by pathological examination in 53.5% of the samples, which was similar to the majority of the other series (range 34 to 58%) 11. Peritumoral inflammation may result in adhesions that are indistinguishable from true malignant invasion of proximal organs and structures during the surgical procedure.…”
Section: Discussionsupporting
confidence: 88%
“…However, the two series with predominantly male patients reported morbidity rates of 24% and 50% 3,10. These results were not significantly different from those of studies not composed predominantly of male patients, such as the current study (morbidity ranged from 25-48%) 9,11-13.…”
Section: Discussioncontrasting
confidence: 69%
“…Despite extensive preoperative evaluation, the decision to perform a multivisceral resection is often made intraoperatively [3]. The cornerstones of managing patients with multivisceral disease are a meticulous search for metastases, a wide en bloc resection and minimal tumour manipulation [23,32].…”
Section: Colonmentioning
confidence: 99%
“…About 10% of all colorectal cancers are either adherent to or invading contiguous organs at presentation [2,3]. Of the estimated 180,000 cases of colorectal cancer annually diagnosed in the EU, approximately 15% are locally advanced, and isolated locoregional recurrence occurs in approximately 5%.…”
Section: Introductionmentioning
confidence: 99%
“…Minimal invasive surgery reproduced similar long-term outcomes to those after open colectomy for primary cancer. It is anticipated that minimal invasive surgery will become the standard of treatment for locally advanced primary cancers [14,15]. A laparoscopic approach in recurrent cancers is controversial as previous laparotomies increase its difficulty.…”
Section: Technical Aspects and Detailsmentioning
confidence: 99%